Evaluation of The Dimensions and Thickness of The Adi Soemarmo Surakarta Airport Apron Pavement Using The FAA (Federal Aviation Administration) Method - Andika Andika; Latif Budi Suparma; Suryo Hapsoro Tri Utomo (Green Publisher Indonesia, 2023)
Air transportation is the most recent mode of transportation among other modes and only emerged and developed in the 20th century. World Wars I and II gave a great impetus to the development of air transport in almost every country in the world. To make it easier to conduct this research, it is necessary to collect data related to